Dewaluacja waluty miejscowej jako instrument polityki rolnej w krajach Sahelu Afryki Zachodniej - Niang, Abdoulaye (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1999)
In the 90. the fast growth of the population in the Sahel countries caused the lack of potential arab le lands. Besides, the international circumstances were not good for agriculture in Africa. Many African countries were looking for solution to the agricultural problems. The Bretton Woods institutions such as IMF (International Monetary Fund) forced the countries of the franc zone to devaluate their currency – “the franc CPA" (Communaute agrarise Africaine - African Monetary Community) in order to promote their export, that in these countries is dominated by agricultural products. The devaluation in some countries, like Senegal, caused the opposite effect. The prices of agricultural products didn't rise, while the prices of the machines and inputs grew highly. The Senegalese government used the 25 % of the growth of prices to balance its budgetary deficit. In opposite to the case of Senegal, the devaluation helped the agricultural sector in Burkina Faso and in Mali. In these countries, after the devaluation by 50%, the imported agricultural products became more expensive than domestic ones. Also thanks to the good conjuncture on the international market the main export crops (the cotton and the peanuts) of these countries were cheaper. The farmers used earnings from the export of these products to buy inputs and machines for the production of cereals.